Interaction of the hepatitis B virus X protein with the lysine methyltransferase SET and MYND domain‐containing 3 induces activator protein 1 activation. (January 2016) - Hayashi, Miwako; Deng, Lin; Chen, Ming; Gan, Xiang; Shinozaki, Kenta; Shoji, Ikuo; Hotta, Hak
ABSTRACT: Hepatitis B virus (HBV) is a widespread human pathogen that often causes chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. The detailed mechanisms underlying HBV pathogenesis remain poorly understood. The HBV X protein (HBx) is a multifunctional regulator that modulates viral replication and host cell functions, such as cell cycle progression, apoptosis and protein degradation through interaction with a variety of host factors. Recently, the nonstructural protein 5A (NS5A) of hepatitis C virus has been reported to interact with methyltransferase SET and MYND domain‐containing 3 (SMYD3), which is implicated in chromatin modification and development of cancer. Because HBx shares fundamental regulatory functions concerning viral replication and pathogenesis with NS5A, it was decided to examine whether HBx interacts with SMYD3. In the present study, it was demonstrated by co‐immunoprecipitation analysis that HBx interacts with both ectopically and endogenously expressed SMYD3 in Huh‐7.5 cells. Deletion mutation analysis revealed that the C‐terminal region of HBx (amino acids [aa] 131–154) and an internal region of SMYD3 (aa 269–288) are responsible for their interaction. Immunofluorescence and proximity ligation assays showed that HBx and SMYD3 co‐localize predominantly in the cytoplasm. Luciferase reporter assay demonstrated that the interaction between HBx and SMYD3 activates activator protein 1 (AP‐1) signaling, but not that of nuclear factor‐kappa B (NF‐κB). On the other hand, neither overexpression nor knockdown of SMYD3 altered production of HBV transcripts and HBV surface antigen (HBsAg). In conclusion, a novel HBx‐interacting protein, SMYD3, was identified, leading to proposal of a novel mechanism of AP‐1 activation in HBV‐infected cells.